Accounting and Finance Graduate Employment Outcomes: Underemployment, Self‐employment and Managing Diversity. Issue 3 (25th July 2018) - Jackson, Denise
Abstract: The employment landscape for new graduates is increasingly challenging due to rapid changes in automation and globalisation, coupled with softening labour markets arising from economic uncertainty. For accounting and finance, there is the added complexity of a shift away from traditional core responsibilities and evidence of marginalisation among certain groups within the professions. The study used national data ( N = 40 141) to examine the employment outcomes of accounting and finance graduates in Australia. Findings indicate weak full‐time, short‐term employment outcomes among graduates with little variation in recent years. High levels of casual working were evidenced and the proportion of self‐employed was relatively low in comparison with the broader workforce and was dominated by male and older graduates. Of those working, 45% were not in graduate‐level employment. There were variations in patterns of employment and underemployment by individual characteristics. The study informs stakeholders of prevalent employment trends and determinants of postgraduation outcomes in accounting and finance graduates, in addition to insights into how these professions are progressing in managing diversity. Implications for stakeholders in relation to improving graduate employment outcomes, as well managing diversity, are discussed. Abstract : National data (N = 40, 141) was used to examine the employment outcomes of Accounting and Finance graduates in Australia. Findings indicated weak full‐time, short‐term employment outcomes and high levels of casual and part‐time working. Of those working, only 55% were in graduate‐level employment. There were variations in employment patterns by individual characteristics.